How did the Persian king of kings get his wine? : the upper Tigris in antiquity (c.700 BCE to 636 CE) /: the upper Tigris in antiquity (c.700 BCE to 636 CE). (2018) - Comfort, Anthony; Marciak, Michał
No abstract available